Comparative Evaluation of Interest-Earning Digital Banking Platforms in the Philippines Using Time Value of Money and Multi-Criteria Analysis - Nathan Ama (Academic Bright Collaboration, 2026)
Digital banking platforms in the Philippines offer interest-bearing deposit products with substantially different rates, conditions, costs, and liquidity arrangements. However, advertised rates do not necessarily represent the returns that depositors can realistically obtain after taxation and inflation. This study comparatively evaluates the long-term wealth accumulation potential of Philippine digital banking platforms using the Time Value of Money (TVM) and multi-criteria analysis. A quantitative comparative design was applied to 12 deposit products offered by 10 Philippine banking institutions, with product data verified as of June 2026. Future value and present value were calculated for a standardized ₱100,000 deposit over ten years using annual compounding and a 20% withholding tax. A five-criterion framework assessed effective net yield, accessibility, transaction-cost efficiency, regulatory safety, and liquidity, while three alternative weighting scenarios tested ranking robustness. Inflation-adjusted returns were estimated using the Fisher equation and a 4.5% inflation benchmark. Maya Bank Boosted generated the highest theoretical ten-year future value of ₱310,584.82, although this represents a conditional upper-bound scenario requiring continuous mission compliance. Tonik Solo Stash and OwnBank obtained the highest composite scores of 4.48 and remained robust across the sensitivity scenarios. Tonik’s 12-Month Time Deposit generated ₱85,958.61 in net interest and was the only realistically attainable product with a positive real return of 1.82%. All fully liquid, unconditional savings products produced negative real returns. The findings demonstrate that platform selection should balance after-tax yield with accessibility, costs, safety, and liquidity rather than rely solely on advertised interest rates.